2019
DOI: 10.1016/j.nicl.2019.101908
|View full text |Cite
|
Sign up to set email alerts
|

High interictal connectivity within the resection zone is associated with favorable post-surgical outcomes in focal epilepsy patients

Abstract: Patients with drug-resistant focal epilepsy are often candidates for invasive surgical therapies. In these patients, it is necessary to accurately localize seizure generators to ensure seizure freedom following intervention. While intracranial electroencephalography (iEEG) is the gold standard for mapping networks for surgery, this approach requires inducing and recording seizures, which may cause patient morbidity. The goal of this study is to evaluate the utility of mapping interictal (non-seizure) iEEG netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 47 publications
(55 reference statements)
5
38
0
Order By: Relevance
“…Our approach builds on our previous work with intracranial EEG, where we show that patients generally have better seizure outcomes when high-strength nodes are surgically removed (27)(28)(29)(30). Other groups have reported similar findings from intracranial EEG (31)(32)(33)(34)(35)(36)(37). With MEG data, Nissen et al (9) showed in a cohort of 22 patients, that interictal source localized network hubs overlapped with the resection in seizure-free patients only.…”
Section: Discussionsupporting
confidence: 53%
“…Our approach builds on our previous work with intracranial EEG, where we show that patients generally have better seizure outcomes when high-strength nodes are surgically removed (27)(28)(29)(30). Other groups have reported similar findings from intracranial EEG (31)(32)(33)(34)(35)(36)(37). With MEG data, Nissen et al (9) showed in a cohort of 22 patients, that interictal source localized network hubs overlapped with the resection in seizure-free patients only.…”
Section: Discussionsupporting
confidence: 53%
“…We calculated functional connectivity using a pipeline that we have previously described and validated 10,14,16 . We used intracranial EEG stored on ieeg.org, a cloud-based platform for electrophysiologic data 24,25 .…”
Section: Connectivity Calculationmentioning
confidence: 99%
“…We randomly selected an interictal segment of > 2 minutes for each patient that occurs at least 1 hour away from clinically-annotated seizures; the segment length is justified by prior evidence that even short interictal segments accurately capture critical network patterns in epilepsy 29 . We divided the interictal epoch into one-second intervals ( Figure 1A) and for each window calculated connectivity using coherence in the beta (15-40 Hz) band, which we have previously shown to be effective at detecting abnormal connectivity 10 . We computed the mean of each edge over time to obtain a single adjacency matrix for each patient ( Figure 1B).…”
Section: Connectivity Calculationmentioning
confidence: 99%
See 2 more Smart Citations